3111 Heart Rate Variability as a Predictor of Post-Operative Cognitive Dysfunction in Older Adults. (27th March 2019) - Oyeyemi, Deborah; Berger, Miles; Roberts, Kenneth C.; Giattino, Charles M.; Woldorff, Marty G.; Colon-Emeric, Cathleen; Devinney, Michael J.; Bunning, Thomas; Zhou, Junhong; Lipsitz, Lewis A.; Whitson, Heather E.
Abstract : OBJECTIVES/SPECIFIC AIMS: The objective of this project is to determine whether HRV, collected peri-operatively, is predictive of cognitive decline among older adults who undergo elective surgery/anesthesia. METHODS/STUDY POPULATION: This project is a part of the ongoing INTUIT/PRIME study, which is collecting pre- and post-operative cognitive testing, fMRI imaging, CSF samples, and EEG recordings from 200 older adults (age ≥ 60) undergoing elective non-cardiac/non-neurologic surgery scheduled to last > 2 hours at Duke University Medical Center and Duke Regional Hospital. This project utilizes data from the first 60 INTUIT participants who contributed continuous heart rate data before and during surgery. Participants undergo cognitive testing prior to surgery (baseline) and at 6 weeks after surgery. Our primary dependent variable is the change in the composite score from baseline to 6-weeks. Delirium is assessed in the hospital with the twice daily 3D-CAM tool, so we will report the proportion of individuals with 6-week cognitive decline who exhibited delirium in the days following surgery. Participants' echocardiogram (ECG) recordings are extracted pre- and intraoperatively from B650/B850 patient monitors with VSCapture software. HRV is defined as the variability between successive R-spikes or inter-beat-intervals on ECG. RESULTS/ANTICIPATED RESULTS: We anticipate that lower intraoperative HRV is associated with worse cognitive decline at 6 weeks after surgery. As secondary objectives, we will determine whether pre-operative HRV or change in HRV (from pre-operative to intra-operative measures) are predictive of cognitive decline after surgery. We expect that in-hospital delirium will be detected in a higher proportion of those with 6-week cognitive decline, compared to those with stable or improved cognition at 6 weeks. DISCUSSION/SIGNIFICANCE OF IMPACT: HRV may address the present need for pre- and intra-operative cognitive risk stratification in the elderly. Physiological indices like HRV have the potential to dramatically change our understanding of CI in older adults undergoing surgery, as they offer an accessible, cost-effective, and non-invasive means whereby clinicians, particularly those unfamiliar with the nuances of geriatric and CI/dementia-related care, can monitor patients and refer those at high-risk of CI after surgery for early intervention.